Uncommon thioether-modified metal–organic frameworks with unique selective CO2 sorption and efficient catalytic conversion. Issue 6 (22nd January 2021) - Wang, Wen-Juan; Liu, Jiao; Yan, Yang-Tian; Yang, Xiao-Li; Zhang, Wen-Yan; Yang, Guo-Ping; Wang, Yao-Yu
Abstract : Two novel 3D MOFs were synthesized successfully. In particular, MOF 1 was found to selectively adsorb CO2 from the mixture of CH4 /CO2 and perform as an excellent recyclable catalyst to fix CO2 into cyclic carbonate. Abstract : Two new three-dimensional (3D) metal–organic frameworks (MOFs), namely {[Cu2 (L)(4, 4′-bipy)(OH)]·H2 O} n (1 ) and {[Mn3 (L)2 (4, 4′-bipy)(DMA)2 ]·H2 O} n (2 ), were constructed by a newly synthesized thioether carboxylic acid ligand 5-((formic acid-3-sulfur)methyl)isophthalic acid (H3 L) and 4, 4′-bipyridine (4, 4′-bipy). Thioether bonds in H3 L can rotate freely in space, which are conducive in constructing MOFs with rich and stable structures. Simultaneously, the uncoordinated sulfur atoms affect the polarity of the framework and play an important role in adsorption. Gas adsorption results indicated that 1 can selectively adsorb CO2 from the mixture of CH4 /CO2 . Moreover, due to the high catalytic activity of [Cu4 (COO)6 N4 O2 ] clusters, 1 is also an excellent recyclable catalyst that can chemically fix CO2 into cyclic carbonate under mild solvent-free conditions. Therefore, 1 may be explored as a dual-functional material for industrial adsorption and catalysis.